Gene delivery potential of biofunctional carbonate apatite nanoparticles in lungs - Alhaji, Suleiman Yusuf; Chowdhury, Ezharul Houque; Rosli, Rozita; Hassan, Fatma; Abdullah, Syahrilnizam (Hindawi Publishing Corporation, 2014)
Existing nonviral gene delivery systems to lungs are inefficient and associated with dose limiting toxicity in mammalian cells. Therefore, carbonate apatite (CO3Ap) nanoparticles were examined as an alternative strategy for effective gene delivery to the lungs. This study aimed to (1) assess the gene delivery efficiency of CO3Ap in vitro and in mouse lungs, (2) evaluate the cytotoxicity effect of CO3Ap/pDNA in vitro, and (3) characterize the CO3Ap/pDNA complex formulations. A significantly high level of reporter gene expression was detected from the lung cell line transfected with CO3Ap/pDNA complex prepared in both serum and serum-free medium. Cytotoxicity analysis revealed that the percentage of the viable cells treated with CO3Ap to be almost similar to the untreated cells. Characterization analyses showed that the CO3Ap/pDNA complexes are in a nanometer range with aggregated spherical structures and tended to be more negatively charged. In the lung of mice, highest level of transgene expression was observed when CO3Ap (8 μL) was complexed with 40 μg of pDNA at day 1 after administration. Although massive reduction of gene expression was seen beyond day 1 post administration, the level of expression remained significant throughout the study period.